Japanese diasporas : unsung pasts, conflicting presents, and uncertain futures - Adachi, Nobuko (London ; New York : Routledge/Taylor & Francis Group, 2006)
An examination of the relationship of overseas Japanese and their descendents (Nikkei) with their home and host nations, focusing on their political, social and economic struggles. The authors suggest some of the ways in which diasporas are transforming global society today.--
Introduction -- Japanese diaspora in New World: its Asian predecessors and origins / Roger Daniels -- Japanese emigration and immigrations: from the Meiji to the modern / James Stanlaw -- Instructions to emigrant laborers, 1885-94: "return in triumph" or "wander on the verge of starvation" / Jonathan Dresner -- Paradise lost: Japan's agricultural colonists in Manchukuo / Greg P. Guelcher -- Intermarried issei and mestizo Nisei in the Philippines: reflections on the origin of Philippine nikkeijin problems / Shun Ohno -- Constructing Japanese Brazilian identity: from agrarian migrants to Urban white-collar workers -- Stone voice: diary of a Japanese transnational migrant in Canada / Keibo Oiwa -- Japanese of Peru: first-century experience and beyond / Daniel M. Masterson -- Japanese Latin Americans during World War II: a reconsideration / Lane Ryo Hirabayashi and Akemi Kikumura-Yano -- Four governments and a new land: emigration to Bolivia / Kozy Amemiya -- Acting Japanese / Gary Y. Okihiro -- Crossing ethnic boundaries: challenge of Brazilian Nikkeijin return migrants in Japan / Takeyuki Tsuda -- Overseas Japanese and the challenges of repatriation in post-colonial East Asia / Mariko Asano Tamanoi -- Negotiating work and self: experiences of Japanese working women in Singapore / Leng Leng Thang, Miho Goda, and Elizabeth Maclachlan
Includes bibliographical references (pages 254-273) and index.
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Chōsen Kōgei Kenkyūkai; Geschichte; Geschichte; Japanese -- Foreign countries; Japanese -- Canada -- Emmigration and immigration; 74.94 migration (demography); Emigration and immigration; Japanese -- Foreign countries; Ausland; Auswanderung; Kulturelle Identität; Diaspora; Japan; Japan -- Emigration and immigration; Japan